Case Study of Building Information Modeling Implementation in Infrastructure Projects. Issue 2 (February 2022) - Guo, Xingzhou; Tian, Chi; Chen, Yunfeng; Zhang, Jiansong
Building information modeling (BIM) has been advocated as a potential solution to many challenges of asset management, such as missing data, incompatible software, and unclear business process. However, its current implementation in infrastructure projects has only accounted for technology application and digital information delivery without considering system compatibility or information need. More significantly, BIM implementation requires compatible development of various aspects of a business, a gap in which can lead to different implementation levels or even project failure. Limited research is available on the key factors and challenges of BIM implementation in infrastructure projects. Therefore, this study aims to present a case study with particular emphasis on interviews with key stakeholders to explore the main challenges and solutions of BIM implementation. It starts with the development of interview questionnaires based on literature review and feedback from a research team composed of key stakeholders. Interviews were conducted with 37 professionals from stakeholders of the owner, designers, contractors, and software vendors. Four main factors and challenges, along with potential solutions, were identified from content analysis of the interviews: (i) isolation of project phases (process factor), (ii) incompatibility of project technologies and interfaces (technology factor), (iii) unclear definition of requirements and responsibilities of project stakeholders (people factor), and (iv) imperfect information collection and sharing (information factor). The four factors dictate "when, ""how, " and "what" information should be collected and communicated by "whom, " which are mutually interdependent, and focusing on limited factors instead of all four can compromise the successful implementation of BIM.